A Dietary Supplement Containing Micronutrients, Phosphatidylserine, and Docosahexaenoic Acid Counteracts Cognitive Impairment in D-Galactose-Induced Aged Rats - Ren, Qian; Sun, Jianqin; Xu, Danfeng; Xie, Hua; Ye, Mengyao; Zhao, Yanfang (Frontiers in Nutrition, 2022)
At present, it is a trend to use dietary supplements to prevent age-related cognitive impairment. This study aimed to investigate the effects of a dietary supplement enriched with micronutrients, phosphatidylserine, and docosahexaenoic acid on cognitive performance using a D-galactose (D-gal) induced aging rat model. Seven-month-old male Sprague-Dawley rats were randomly divided into five groups, including the control group, D-gal model group, and low-dose (2 g/kg body weight), medium-dose (6 g/kg bw), and high-dose (10 g/kg bw) dietary supplement intervention groups, which were investigated for 13 weeks. The dietary supplement intervention was found to improve cognitive performance in Morris water maze test, increase superoxidase dismutase activity, reduce malondialdehyde activity, increase tumor necrosis factor-α and interleukin-6 concentrations, inhibit the activation of astrocytes, and elevate brain-derived neurotrophic factor protein and mRNA expression in the brains of D-gal-induced aged rats. This dietary supplement customized for the aged can be applied to the restoration of cognitive performance by enhancing antioxidant and anti-neuroinflammatory abilities, up-regulating neurotrophic factor, and inhibiting the activation of astrocytes. These results will be useful for future studies focused on implementation in humans.